Synergistic effects of Rho kinase inhibitor Y‐27632 and Noggin overexpression on the proliferation and neuron‐like cell differentiation of stem cells derived from human exfoliated deciduous teeth. Issue 4 (30th December 2019) - Yang, Si; Xin, Cuijuan; Zhang, Bo; Zhang, Hongbo; Hao, Yunpeng
Abstract: Stem cells from human exfoliated deciduous teeth (SHEDs) are highly proliferative, clonogenic, and multipotent stem cells with a neural crest cell origin. This property could be a desirable option for potential therapeutic applications. In this study, we focus on the effects of Rho kinase inhibitors Y‐27632 and Noggin on the proliferation of SHEDs and their differentiation into neuron‐like cells. SHEDs were extracted from 10 samples of deciduous teeth obtained from healthy children aged from 5 to 10. The passaged SHEDs were transfected with Noggin, Y‐27632, or their combination. By means of MTT and colony formation assays, the effects of Y‐27632 and Noggin on cell viability and colony formation were detected. Cellular morphology and neurosphere formation were observed under a microscope. Y‐27632 transfection in SHEDs showed enhanced cell viability, colony formation, and neurosphere formation indicating that Y‐27632 could promote cell proliferation of SHEDs. Furthermore, we observed that the SHEDs treated with Noggin in combination with Y‐27632 displayed typical neuron‐like cell morphology and reticular processes. Noggin or Y‐27632 alone or in combination induced obviously increased NSE, Nestin, and GFAP levels, which were highest in SHEDs treated with the combination of Noggin and Y‐27632. These findings suggest that Y‐27632 promotes the proliferation of SHEDs, and Y‐27632 and Noggin in combination have a synergistic effect on promoting differentiation of SHEDs into neuron‐like cells.